Savory baking : recipes for breakfast, dinner, and everything in between - McDowell, Erin Jeanne (Harvest, an imprint of William Morrow, 2022)
"From the New York Times bestselling author of The Book on Pie and The Fearless Baker, a savory baking book for delicious baked goods at any time of day"--